PROSPECTIVE STUDY: A COMPARISON OF TRADITIONAL BLEPHAROPLASTY AND COLD PLASMA BLEPHAROPLASTY - Munirakhon S. Kasimova,; Mufazzalkhon M. Iminova, (Central Asian Journal of Medicine, 2025)
The aim of this prospective study is to compare the efficacy and safety of two methods for correcting age-related changes in the eyelids — traditional surgical blepharoplasty and cold plasma blepharoplasty. The study evaluates recovery times, complication rates, aesthetic outcomes, and procedure duration. Results showed that while both methods were effective, cold plasma blepharoplasty demonstrated a faster recovery period and fewer complications. Age-related facial changes, including sagging of the upper and lower eyelids, are a common concern for individuals over the age of 40. Blepharoplasty is an effective surgical procedure used to improve the appearance of the eyes and rejuvenate the face. With advancements in cosmetic surgery, a new technique — cold plasma blepharoplasty — has emerged, utilizing plasma flow to remove excess skin and adipose tissue, in contrast to traditional surgical blepharoplasty. This study aims to compare these two methods across several key parameters.